Linear expectile regression under massive data - Shanshan Song; Yuanyuan Lin; Yong Zhou (Fundamental Research, 2021)
In this paper, we study the large-scale inference for a linear expectile regression model. To mitigate the computational challenges in the classical asymmetric least squares (ALS) estimation under massive data, we propose a communication-efficient divide and conquer algorithm to combine the information from sub-machines through confidence distributions. The resulting pooled estimator has a closed-form expression, and its consistency and asymptotic normality are established under mild conditions. Moreover, we derive the Bahadur representation of the ALS estimator, which serves as an important tool to study the relationship between the number of sub-machines K and the sample size. Numerical studies including both synthetic and real data examples are presented to illustrate the finite-sample performance of our method and support the theoretical results.